Spatial Sampling Strategies for Assessing Public Opinion Under the Water Framework Directive: A Case Study of the Ythan Project - Neil Sang (European Regional Science Association (ERSA), 2004)
Consultation with and inclusion of the public on measures to manage and improve water resources is a key tenet of the Water Framework Directive (WFD). This involves establishing people's opinions but also the perspectives (both metaphoric and literal) which inform these. In particular water is a complex and dynamic spatial entity with many spatial expressions relating to its various functions, so perspectives as to its utility and proper management are equally various. In establishing a catchment rather than discipline based approach to management, the WFD recognises the spatially integrated nature of the issues. It also poses a challenge to research, in that the pattern presented by the interaction between human and biophysical processes is a compound of the complexities of the two systems. Capturing the detail of such a pattern from a sample requires a strategy which is sensitive to the relevant dynamics of each system. This paper considers a case study relating to a postal survey carried out by the Macaulay Institute on behalf of the EU Life Environment Fund's Ythan Project, which aimed to develop wider participation in the protection of the River Ythan (Scotland's first Nitrate Vulnerable Zone). A thousand questionnaires were sent to residents and farmers in the Ythan catchment in spring 2002, for comparison the adjacent River Ugie and the more distant Loch Leven catchments were surveyed the following year. The methodology presented represents the attempt to maximise at the design stage the utility this data would have for analysis of responses in relation to both respondent's social-environs and the proximity of the water body, as well as to ensure a representative over all sample. The somewhat awkward term “water body” highlights the difficulties for the key issue of definition, be that for rivers and lochs, or people, residences and urban areas. The decisions made with regards to definition are explained and results from the survey presented illustrating the practical significance of initial object definitions in conditioning the outcome. The importance of considering spatial aspects post survey is also highlighted. Keywords: Spatial, Sampling, Water Framework Directive, Survey.
Keywords: 330; Spatial; Sampling; Water Framework Directive; Survey